Bridge monitoring system based on Internet of things technology - Zheng LI; Sheng ZHANG; Luyu ZHANG; Yang ZHANG (物联网学报)
The Internet of everything is the trend of today’s smart cities.With the rapid development of Internet of things technology,a good opportunity is provided to obtain real-time status information on important infrastructures.Aiming at the problem such as low monitoring efficiency,poor flexibility and rigorous testing results with traditional artificial bridge monitoring methods a bridge monitoring system based on the Internet of things technology was designed.A variety of sensors and cameras were used in the system to collect the data of bridge’s dynamic status in real-time,and the wireless multi-hop network was used to transfer the perception data to the bridge health monitoring cloud platform for further processing and analysis.Real-time monitoring,early warning,analysis and assessment of bridge safety conditions could be realized by the system,and is very important to the bridge safety engineering.